TRIM8 inhibits porcine epidemic diarrhoea virus replication by targeting and ubiquitinately degrading the nucleocapsid protein - Zhenbin Bi; Wei Wang; Shanshen Gu; Yajing Zhou; Zhengchang Wu; Wenbin Bao; Haifei Wang (Veterinary Research)
Abstract Porcine epidemic diarrhoea virus (PEDV) is an enteric pathogen that causes acute diarrhoea, dehydration and high mortality rates in suckling pigs. Tripartite motif 8 (TRIM8) has been shown to play multiple roles in the host’s defence against viral infections. However, the functions of TRIM8 in regulating PEDV infection are still not well understood. In our study, we found a significant upregulation of TRIM8 following PEDV infection. We created TRIM8 knockout and overexpression cell lines and discovered that TRIM8 can inhibit PEDV replication within host cells. Co-immunoprecipitation assays revealed that TRIM8 directly interacts with the nucleocapsid protein (N) of PEDV, specifically within the coiled-coil structural domain of TRIM8. Furthermore, TRIM8 was shown to reduce the expression of the PEDV N protein in a dose-dependent manner. Mechanistically, TRIM8 inhibits the expression of PEDV N through K48-linked ubiquitin proteasome degradation. Transcriptomics analysis revealed that TRIM8 facilitates the expression of genes associated with several pathways, including the IL-17 signalling pathway, chemokine signalling pathway, and cytokine-cytokine receptor interaction. This suggests that TRIM8 plays a crucial role in boosting antiviral immune responses against PEDV infection. Our findings provide new insights into the functions and mechanisms of TRIM8 in regulating PEDV infection and highlight its potential as a molecular target for the prevention and control of this virus.